SECONDARY SCHOOL STUDENTS’ ATTITUDE TOWARDS PHYSICS BASED ON GENDER AND GRADE LEVEL DIFFERENCES - Andrie Chaerul (Wahana Karya Ilmiah Pendidikan, 2020)
The main purpose of the present study is to investigate the differences on students’ attitudes toward Physics based on gender and grade level among Senior Secondary Education students. A group of approximately 864 male and female in eleventh- and twelfth-grade students, equally proportioned by gender were assigned to take part in this study. A standardized instrument namely The Test of Science Related Attitudes (TOSRA) questionnaire has been employed to collect data. A two-way Analyses of Variance (ANOVA) was used to quantitatively analyze the collected data. The study found that in general, male students do show more positive attitudes toward Physics than their female counterparts. Regarding grade level, twelfth grader show more positive attitudes toward Physics than eleventh graders. Keywords: TOSRA, attitude towards science, gender, grade level